Anthropometric characteristics, physical attributes, and relative age effect of elite youth soccer players: comparison between Iceland and Norway - Arnór Snær Guðmundsson 1993- (2022)
Introduction: Soccer is one of the world’s most popular sports. Performance in soccer is dependent on physical, technical, tactical, and mental factors. In youth soccer, performing a testing battery is key to monitor progress and load, as well as developing training plans and seeing its effect. Objectives: To analyse and compare anthropometric characteristics, physical fitness attributes, and relative age effect of elite youth players in Iceland and Norway. Method: 46 players from the Icelandic male youth national teams and 26 players from an elite Norwegian academy participated. Participants performed anthropometric measurements (height and weight) and seven physical fitness tests, 5x30m repeated sprint ability test, which included measurements of 10- and 30-meter sprint time, countermovement jump, Abalakov jump, the Illinois agility test, and the YoYo intermittent recovery test level 2. To analyse difference between groups, independent sample t-test was used while chi-square was used to analyse results based on date of birth. Results: There were no differences between Icelandic and Norwegian players in anthropometric characteristics. There were differences where Icelandic players performed better than Norwegian players (p<0.05) in: the 5x30m repeated sprint test, countermovement jump, 10- and 30-meter sprint, and the Illinois agility test. Relative age effect was found in neither of the groups. Conclusion: Icelandic and Norwegian elite youth players in this study possess similar anthropometric characteristics. On the other hand, Icelandic youth elite players seem to have better physical fitness qualities as participants in this study performed better on various physical fitness tests. This study indicates that RAE is not prevalent in elite youth soccer players in Iceland and Norway. Keywords: Soccer, youth, elite, physical testing, physical performance, relative age effect, Iceland, Norway Inngangur: Fótbolti er ein af vinsælustu íþróttum heims. Frammistaða í fótbolta er háð líkamlegum, tæknilegum, ...